2017
DOI: 10.1104/pp.16.01962
|View full text |Cite
|
Sign up to set email alerts
|

Poplar MYB115 and MYB134 Transcription Factors Regulate Proanthocyanidin Synthesis and Structure

Abstract: The accumulation of proanthocyanidins is regulated by a complex of transcription factors composed of R2R3 MYB, basic helix-loop-helix, and WD40 proteins that activate the promoters of biosynthetic genes. In poplar (genus Populus), MYB134 is known to regulate proanthocyanidin biosynthesis by activating key flavonoid genes. Here, we characterize a second MYB regulator of proanthocyanidins, MYB115. Transgenic poplar overexpressing MYB115 showed a highproanthocyanidin phenotype and reduced salicinoid accumulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 78 publications
(125 reference statements)
4
103
0
Order By: Relevance
“…CHS , chalcone synthase; CHI , chalcone isomerase; F3H, flavanone 3‐hydroxylase; DFR , dihydroflavonol reductase; FLS , flavonol synthase; LAR , leucoanthocyanidin reductase; ANS , anthocyanidin synthase; ANR , anthocyanidin reductase. Note that MYB 134 and MYB 115 positively regulate PA synthesis in association with the basic helix–loop–helix enzyme bHLH 131 (James et al ., ). MYB 182 acts as a negative regulator of PA synthesis in poplar (Yoshida et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…CHS , chalcone synthase; CHI , chalcone isomerase; F3H, flavanone 3‐hydroxylase; DFR , dihydroflavonol reductase; FLS , flavonol synthase; LAR , leucoanthocyanidin reductase; ANS , anthocyanidin synthase; ANR , anthocyanidin reductase. Note that MYB 134 and MYB 115 positively regulate PA synthesis in association with the basic helix–loop–helix enzyme bHLH 131 (James et al ., ). MYB 182 acts as a negative regulator of PA synthesis in poplar (Yoshida et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Recently, MYB115 was shown to be another positive regulator of PA synthesis (James et al ., ; Wang et al ., ). These two transcription factors work in association with a bHLH131 transcription factor and a WD40 protein in the poplar MBW complex (James et al ., ). We showed that transcript levels of these regulatory genes increased in both BTH‐treated and SA‐hyperaccumulating lines.…”
Section: Discussionmentioning
confidence: 97%
“…MYB165 and MYB194 were first identified by being upregulated in MYB134 ‐overexpressing transgenic poplars, with overexpression ratios of 3.55‐ and 7.97‐fold, respectively (James et al ., ). MYB165 and MYB194 are paralogs from a whole genome duplication (Chai et al ., ), with 87% DNA sequence similarity and 79% protein sequence similarity between them.…”
Section: Resultsmentioning
confidence: 97%
“…MYB165 showed higher expression in young leaves than in older leaves, stems, and roots. Transcript levels were not significantly different between plants grown in the greenhouse and natural sunlight, a treatment previously shown to induce PA and anthocyanin synthesis (James et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation